Research on particle imaging detectors - Charpak, Georges (World Scientific, 1995)
Much instrumentation has been developed for imaging the trajectories of elementary particles produced in high energy collisions. Since 1968, gaseous detectors, beginning with multiwire chambers and drift chambers, have been used for the visualization of particle trajectories and the imaging of X-rays, neutrons, hard gamma rays, beta rays and ultraviolet photons. This book commemorates the groundbreaking research leading to the evolution of such detectors carried out at CERN by Georges Charpak, Nobel Prizewinner for Physics in 1992. Besides collecting his key papers, the book also includes original linking commentary which sets his work in the context of other worldwide research